2018
DOI: 10.1155/2018/2580171
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Finite Element Method for Analyzing the Sensitivity of Graphyne-Based Resonators

Abstract: An atomic-scale finite element method was applied to analyze the sensitivities of α-, β-, γ-, and 6,6,12-graphyne-based resonators in mass detection under different boundary conditions. These sensitivities are then compared with that of a graphene-based resonator obtained in a previous study. According to the analysis results, among the graphyne-based resonators, the α type shows the highest sensitivity, while the γ type shows the lowest. In addition, the sensitivity decreases as the resonator size increases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…They conducted uniaxial and biaxial tensile simulations using computational models of zigzag and armchair configurations and compared their results with equivalent molecular dynamics and density functional theory models, finding that they were in good agreement. Lee et al [29] applied an atomistic FE model to analyze the sensitivity of various graphyne-based resonators under different boundary conditions and size configurations. They compared the results with those of graphene-based resonators and concluded that graphyne derives higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…They conducted uniaxial and biaxial tensile simulations using computational models of zigzag and armchair configurations and compared their results with equivalent molecular dynamics and density functional theory models, finding that they were in good agreement. Lee et al [29] applied an atomistic FE model to analyze the sensitivity of various graphyne-based resonators under different boundary conditions and size configurations. They compared the results with those of graphene-based resonators and concluded that graphyne derives higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…MD has been also utilised [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] for the investigation of the mechanical response of various graphyne structures. It is worth noting that even though there are several first-principles and MD computations concerning two-dimensional graphynes, only some reports are associated with SM-based approaches for graphynes [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Still, most of these theoretical analyses, which are grounded on SM, concentrate on the calculation of the linear elastic properties of graphynes.…”
Section: Introductionmentioning
confidence: 99%